EXPLORATION OF LOCAL WISDOM IN CORN CULTIVATION (ZEA MAYS L. SACCHARATA STURT) IN INCREASING FARMERS’ INCOME IN SEI SIARTI VILLAGE, PANAITENGAH DISTRICT, LABUHANBATU REGENCY - Jasman Hasibuan; Khairul Rizal; Ika Ayu Putri Septyani; Fitra Syawal Harahap; Deci Irmayani (RADJA PUBLIKA, 2024)
This study aims to analyze the potential integration of local wisdom in corn cultivation practices in Sei Siarti Village to improve farmers' welfare and support environmental sustainability. The research method involved field surveys, interviews, and observations of cultivation structures and natural resource management systems. The data were analyzed using multiple linear regression to evaluate the relationship between the application of local wisdom and farmers' income enhancement. The findings reveal that traditional practices, such as selecting adaptable crop varieties, eco-friendly soil management techniques, and natural pest control methods, contribute to sustainable productivity while maintaining ecosystem balance. Integrating local knowledge with modern agricultural technology is expected to enhance food security and improve the quality of life for farmers in the future. Therefore, government support and training in the application of environmentally friendly technology is highly recommended.